Treatment of early-stage breast cancer with percutaneous thermal ablation, an open-label randomised phase 2 screening trial: rationale and design of the THERMAC trial - Erwin Birnie; Cornelis Verhoef; Reno Debets; Taco M A L Klem; Adriaan Moelker; Elles M F van de Voort; Gerson M Struik; Linetta B Koppert; Glenn Yo; Maura J P V Macco; Renata H J A Sinke; Martine Franckena (BMJ Open, 2021)
Introduction Breast cancer is the most frequently diagnosed malignancy worldwide but almost half of the patients have an excellent prognosis with a 5-year survival rate of 98%–99%. These patients could potentially be treated with thermal ablation to avoid surgical excision, reduce treatment-related morbidity and increase patients’ quality of life without jeopardising treatment effectiveness. Previous studies showed highest complete ablation rates for radiofrequency, microwave and cryoablation. However, due to heterogeneity among studies, it is unknown which of these three techniques should be selected for a phase 3 comparative study.Methods and analysis The aim of this phase 2 screening trial is to determine the efficacy rate of radiofrequency, microwave and cryoablation with the intention to select one treatment for further testing in a phase 3 trial. Additionally, exploratory data are obtained for the phase 3 trial. The design is a multicentre open-label randomised phase 2 screening trial. Patients with unifocal, invasive breast cancer with a maximum diameter of 2 cm without lymph node or distant metastases are included. Triple negative, Bloom-Richardson grade 3 tumours and patients with an indication for neoadjuvant chemotherapy will be excluded. Included patients will be allocated to receive one of the three thermal ablation techniques. Three months later surgical excision will be performed to determine the efficacy of thermal ablation. Treatment efficacy in terms of complete ablation rate will be assessed with CK 8/18 and H&E staining. Secondary outcomes include feasibility of the techniques in an outpatient setting, accuracy of MRI for complete ablation, patient satisfaction, adverse events, side effects, cosmetic outcome, system usability and immune response.Ethics and dissemination This study protocol was approved by Medical Research Ethics Committee of the Erasmus Medical Center, Rotterdam, the Netherlands. Study results will be submitted for publication in peer-reviewed journals.Trial registration number NL9205 (www.trialregister.nl); Pre-results.